EMPLOYEE PERFORMANCE ASSESSED FROM WORK ETHOS, ORGANIZATIONAL CULTURE AND EMOTIONAL INTELLIGENCE IN THE DEPARTMENT OF TRADE OF SURAKARTA CITY - Muniroh, Fitri Ita (JIMEK : Jurnal Ilmiah Mahasiswa Ekonomi, 2021)
This research aims to determine the effect of employee performance in terms of work ethic, organizational culture, and emotional intelligence at the Surakarta City Trade Office. The sample in this study used purposive sampling technique which resulted in a sample of 45 employees of the Surakarta City Trade Office. Techniques for obtaining data using questionnaire techniques. Associative research method with data analysis techniques using validity,mreliability, classical assumptions, multiple regression analysis and hypothesis testing. Themresults showed that simultaneously work ethic, organizational culture, and emotional intelligence had a positive and significant effect on employeemperformance while partially workmethic had no effect on employee performance, on the other hand, organizational culture and emotional intelligence had an effect on employee performance